4CPS-028 Educating cardiac rehabilitation patients on their medicines. (2nd March 2018) - Silvari, V; Coman, E; Keating, A; Lynch, D; McCarthy, S
Abstract : Background: Educating patients on their medications is a core component of the cardiac rehabilitation programme. Purpose: This study investigated the effectiveness of medicine management education and educational videos within a cardiac rehabilitation programme. This was evaluated in terms of patient knowledge of, belief in and adherence to their medicines. Material and methods: The study was conducted over a 6 month period (August 2016 to February 2017). Patients had experienced a cardiac event (myocardial infarction, angioplasty/stent insertion, heart-valve and/or bypass surgery) and were attending phase 3 of Cork University Hospital's (CUH) cardiac rehabilitation programme. Week 1, patients answered a pre-programme questionnaire to assess their knowledge of cardiac medicines. Week 2, patients answered a questionnaire after pharmacist's medicine management education to evaluate the benefit of the education. Week 4, patients were sent videos on their medicines by e-mail. Week 6, patients answered a post-programme questionnaire to evaluate the increased knowledge and adherence to medicines. The pre- and post-programme questionnaires comprised the Morisky 8-item adherence scale and the Beliefs about Medicines Questionnaire (BMQ) along with five questions about medication knowledge. Paired data analysis on pre- and post-programme results was performed using SPSS. Descriptive statistics were used to represent patient responses to the medication management education and the videos. Results: Seventy-six patients evaluated the medicines management education. Ninety-three per cent of patients reported they knew more about why they took their medicines after receiving the education (n=60). The mean score on the BMQ Concern pre-education was 13.72 (n=68) and post-education was 12.62 (n=53) (p=0. 031). A small increase in self-reported adherence from 6.73 (n=66) before education to 6.87 (n=55) post-education was noted. Thirty-one patients evaluated the educational videos, of which 62% found the videos useful/very useful. Conclusion: This study has shown the benefits of medicine management education: patients' increased knowledge of why they take their medicines and significant reduction in their concerns about medicines. The participants who accessed the online educational videos found them to be a useful tool, which is a new way of helping patients educate themselves in CUH. Future work will look to expand the use of the educational videos and to enhance the material on medicine management education. No conflict of interest